COGNITIVE ASPECTS OF REPRESENTATIONS AND PSYCHOEMOTIONAL STATE OF STUDENT YOUTH DURING DISTANCE LEARNING IN A PANDEMIC - Berberyan , A.S. (Modern Psychology, 2021)
The article examines the psychological and pedagogical aspects of distance learning in the higher education system in a pandemic. The methodological basis of our research is the conceptual foundations of the professional formation of a person and activity (B. G. Ananiev, A. G. Asmolov, S. D. Smirnov), the development of modern technologies (A. A. Andreev, E. S. Polat, M. Yu. Bukharkina and others); psychoemotional states of personality (K. Izard, G. Selye), the provisions of humanistic psychology (A. Maslow, K. Rogers, etc.). It is important to study the adaptation and regulation of students' stress. The aim of the research is to study the cognitive aspects of the ideas and psychoemotional states of the personality of students during the period of distance learning in the context of a pandemic. The main research methods are analysis of scientific literature, questionnaires, testing of subjects of educational activity regarding various aspects of online learning in a pandemic and identifying their views. Based on the results of empirical research, the data are interpreted and conclusions are drawn.
Keywords: representations; psychoemotional state; student youth; , distance learning